Analysis of work attitudes and musculoskeletal complaints in laundry workers in bandar kediri - Sumaningrum, Ningsih; Purnadianti, Mely; Rahim, Nureen (Institute Of Computer Science (IOCS), 2024)
Laundry work carries a health risk of muscle problems. Especially in work attitudes, many cases experience musculoskeletal complaints if left unchecked, causing injury, disrupting productivity and even increasing work accidents. The household laundry industry is currently growing rapidly in line with the increasing level of activity in society. The aim of this research is to analyze work attitudes with musculoskeletal complaints in laundry workers in Bandar Kediri. The population and sample are all laundry workers in Bandar Kediri totaling 47 people. The design of this research is cross sectional and uses the Pearson correlation test. The research results showed that there was a significant relationship of 0.027 between work attitudes and musculoskeletal complaints. There is a relationship between work attitudes and musculoskeletal complaints, improving work attitudes will have an impact on changes in musculoskeletal complaints. Ergonomic work attitudes are important to apply in home industry laundry services to avoid musculoskeletal injuries, supported by adequate facilities such as ergonomic ironing tables and performing muscle relaxation movements such as simple twisting exercise 2-3 minutes